2012
DOI: 10.1071/wr11161
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of distance-estimation error during wetland-dependent bird surveys

Abstract: Context The most common methods to estimate detection probability during avian point-count surveys involve recording a distance between the survey point and individual birds detected during the survey period. Accurately measuring or estimating distance is an important assumption of these methods; however, this assumption is rarely tested in the context of aural avian point-count surveys. Aims We expand on recent bird-simulation studies to document the error associated with estimating distance to calling birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Although we demonstrate that simultaneous comparisons of HPC and ARU data potentially enable the calculation of EDR and densities of birds from ARU recordings, this approach still relies on accurate distance estimation during HPCs, an assumption that is frequently violated during avian surveys (Alldredge et al 2007, Nadeau andConway 2012). Errors in distance estimation can bias EDR and bird density calculations and will persist when using our correction approach for ARU data.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrate that simultaneous comparisons of HPC and ARU data potentially enable the calculation of EDR and densities of birds from ARU recordings, this approach still relies on accurate distance estimation during HPCs, an assumption that is frequently violated during avian surveys (Alldredge et al 2007, Nadeau andConway 2012). Errors in distance estimation can bias EDR and bird density calculations and will persist when using our correction approach for ARU data.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately estimating distances of birds to observers and ARUs is difficult to achieve during most avian surveys because birds are often detected aurally instead of visually (Scott et al , Alldredge et al , Nadeau and Conway ). Biased or imprecise distance estimations often result from a combination of localization error (i.e., the ability of an observer to locate a bird) and distance estimation error (i.e., the ability of an observer to accurately estimate distance from the bird to themselves; Alldredge et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Biased or imprecise distance estimations often result from a combination of localization error (i.e., the ability of an observer to locate a bird) and distance estimation error (i.e., the ability of an observer to accurately estimate distance from the bird to themselves; Alldredge et al ). Previous studies have indicated that a suite of factors leads to errors in distance estimation, including habitat structure (Richards and Wiley ), species of the bird (Richards , Schieck , Hobson et al , Alldredge et al , Nadeau and Conway ), distance from the bird to the observer (Nadeau and Conway ), volume of the vocalization (Nadeau and Conway ), orientation of the bird (Alldredge et al ), and various environmental factors such as wind and noise (Simons et al ). These factors can ultimately lead to overestimating distances of birds close to the observer and underestimating distances of birds farther away (Nadeau and Conway ).…”
Section: Discussionmentioning
confidence: 99%
“…Surveyors received training and were reasonably accurate at estimating distance to rails within 225 m ( Fig. 1b in Nadeau and Conway 2012). If no distance was recorded for a given detection (9.4% of detections), we assumed that detection was within 225 m. Our analyses included data from a total of 36,378 surveys conducted at 2473 survey points (mean = 14.71 surveys conducted per survey point).…”
Section: Survey Datamentioning
confidence: 99%